Institutional capacity for standards conformity assessment: A case study on spices in Tanzania - Adam Akyoo; Evelyne Lazaro (Danish Institute for International Studies (DIIS), 2008)
Local capacity for standards conformity assessment is an important component in accessing export markets. In theory, it will lead to lowered compliance costs on the part of local exporters. Moreover, it may provide local exporters with the ability to contest unfavourable foreign test results and thus avoid unnecessary losses. This is important in cases where product contamin-ation occurs outside their borders. This is however possible only where relevant local institutions are accredited and adequately capitalized in terms of laboratory facilities, testing equipment, and certification services. Tanzania spices have four important market destinations - the domestic market, regional markets in Africa, the Asian market, and the EU market. The national standards that were formulated during late 1970s and 1980s address cleanliness and quality standards, and specify microbiological limits for various micro-organisms in spices. These standards are not observed in the local market due to lack of consumer demand for them and the absence of a deliberate industry drive to en-force them. This position weakens the possibility of using conformity to local standards as a step-ping stone to international conformity. Regional markets in Africa and Asian export markets are absorbing spice imports regardless of their quality so issues of conformity assessment in these markets are not important. EU market standards are concerned with food safety. In addition, organically-traded exports must be certified as such. For food safety the main tests demanded are for hazards like aflatoxins, pesticide residues, prohibited chemical dyes, heavy metals, as well as for Salmonella. Conformity assessment for these parameters entails investments in high performance liquid chromatograph, gas chromatograph, and atomic absorption spectrophotometer equipment, as well as other state-of -the-art laboratory facilities. Local conformity assessment in relation to these standards is deficient in many ways. Different approaches are recommended to address this situation. Meeting challenges of international accreditation, harnessing scattered efforts for conformity assessment capacity through improved coordination of existing laboratories, and formulation of a national food safety policy are among the recommendations suggested.
Keywords: 330; Gewürz; Nahrungsmittelbelastung; Normung; Institutionelle Infrastruktur; Tansania